If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 24 = 24 + -9x Reorder the terms: 24 + -6x = 24 + -9x Add '-24' to each side of the equation. 24 + -24 + -6x = 24 + -24 + -9x Combine like terms: 24 + -24 = 0 0 + -6x = 24 + -24 + -9x -6x = 24 + -24 + -9x Combine like terms: 24 + -24 = 0 -6x = 0 + -9x -6x = -9x Solving -6x = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -6x + 9x = -9x + 9x Combine like terms: -6x + 9x = 3x 3x = -9x + 9x Combine like terms: -9x + 9x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| 3(x+2)=32 | | (t-3)2-(t-2)2=5 | | (2x-1)*x=91 | | 70+2m=24m^2 | | 2+a=3(6a-5) | | (2x^2)-4x-30=0 | | (2x-1)x=91 | | r^2+9=6r | | 305+x(5)=350 | | 5x=-37 | | 10=-2x+8 | | 1x+15=25+12x | | -50=19+x | | x+6=-5x+5x | | -7+5=12 | | 6x+42-13x=24 | | x^2+16x+64=-9 | | 7(3x+9)-6(2x+5)= | | 6240000/100= | | 2800+x(150.99)=5819.80 | | -8(2x-4)+7(3+5x)= | | b+3=b*3 | | 6r-6r=-5+r | | A(A-12)-15=30 | | 2y-5+7=-32 | | 2x+10-x+55=90 | | 4.5a=24+2.5a | | b-19=10 | | 13=-3+x | | P=ab+c | | 100/80*78000= | | 7+2(-3n-7)=-4n-21 |